Fraud Diamond Theory Detection on M-Score with Profitability as a Moderating Variable: A Case Study on Sharia Banking Companies - Budiandru; Nur, Basyiruddin (GoAcademica Research & Publishing, 2024)
Financial statements provide information about a company's financial health and performance. Fraud involves deceit created for personal or group gain and can occur within financial reports. The Fraud Diamond model serves as a tool for fraud detection, while the M-Score method detects the financial health of a company. This research explores how profitability influences the relationship between fraud diamond variables and M-Score, aiming to prove whether profitability has an impact on the relationship between at least one fraud diamond variable and M-Score. Moderation Regression Analysis, facilitated by Microsoft Excel and SPSS, is employed as the analytical tool. The study utilizes data samples from Bank Mega Syariah, Bank Syariah Bukopin, Bank Syariah Indonesia, Bank Victoria Syariah, Bank Aladin Syariah, and BPD Riau Kepri Syariah for the period 2020-2022. The findings indicate that profitability strengthens the relationship between independent variables and dependent variables. Moreover, the moderating variable interactions significantly moderate 3 out of 5 X variables against Y. This research aims to fill knowledge gaps, provide deeper understanding, and make a significant contribution to the development of financial management theory. It also offers practical guidance for business stakeholders facing complex and dynamic challenges.